Management of chronic kidney disease. (September 2019) - Tomson, Charlie; Duffy, Samuel
Abstract: Management of chronic kidney disease (CKD) requires a systematic approach including all components of the chronic disease model. Some causes require specific management directed at the underlying cause. For many patients, control of cardiovascular risk factors is the most important intervention, as these also promote progressive loss of kidney function. More intensive control of blood pressure and use of renin–angiotensin axis inhibitors are recommended for patients with diabetes mellitus or significant proteinuria, but excessive blood pressure reduction can be harmful. Reducing the level of proteinuria is an important therapeutic goal. Dietary salt restriction is an important adjunct to drug therapy in preventing fluid retention and reducing cardiovascular burden. Smoking cessation, obesity correction, lipid-lowering treatment and glycaemic control in diabetic patients are also significant. Drug clearance is impaired in CKD, and medication doses often require adjusting in response. Avoiding drugs that are potentially harmful to the kidneys is equally vital. Hypovolaemia and hypotension should be avoided or promptly corrected as they can further damage kidney function. Symptoms are common only in advanced CKD. Patients likely to progress to established renal failure should be referred early enough to allow adequate assessment and preparation for informed decision-making about renal replacement therapy.